TINJAUAN PEMBUKTIAN TINDAK PIDANA KORUPSI OLEH JAKSA PENUNTUT UMUM (Studi Putusan Nomor : 31/Pid.Sus-TPK/2021/PN.Tjk) - Muhammad Arif Fadli Syahputra; B, Erlina; Safitri, Melisa (Maleo Law Journal, 2023)
The Prosecutor's Office carries out a corruption case settlement program to be completed within 3 (three) months and is responsible for the success of the investigation, prosecution and execution of court decisions on corruption cases that have permanent power (in kracht van gewijsde). Problems in researching the form of Prosecution in the Indictment by the Public Prosecutor against the Decision Number: 31/Pid.Sus-TPK/2021/PN.Tjk and how to prove the Corruption Crime by the Public Prosecutor against the Decision Number: 31/Pid.Sus-TPK/ 2021/PN.Tjk. The research method is normative juridical. The form of prosecution in the indictment by the Public Prosecutor against Decision Number: 31/Pid.Sus-TPK/2021/PN.Tjk is to make an indictment that meets the formal requirements that contains the identity of the defendant clearly and completely and material requirements that contain a clear description. and complete details of the criminal act charged with mentioning the time and place where the corruption crime was committed. With the indictment, the public prosecutor delegates the corruption case to the court for examination and a criminal verdict by the Corruption Court. Proof of corruption by the Public Prosecutor against Decision Number: 31/Pid.Sus-TPK/2021/PN.Tjk is through a criminal justice process in court starting with the examination of evidence which is then used by the Public Prosecutor to make a claim. in the form of an indictment to the defendant by looking at the elements of the crime charged against the Defendant.